The Effect of Work Conflict on Teacher Performance in Sinar Harapan Education Foundation. Beringin Deli Serdang Regency - Sopianna Br Purba (Institute of Computer Science (IOCS), 2018)
Sinar Harapan Gang Bali Education Foundation Kec. Beiringin Regency. Deli Serdang is an organization engaged in educational services where the main activity is to hold teaching and learning activities. This study aims to determine how the Effect of Work Conflict on Teacher Performance in the Sinar Harapan Education Foundation. The population and sample used in this study were all teachers for the junior high school level at the Sinar Harapan Education Foundation. The sample of this study amounted to 35 people with two variables, namely Work Conflict (independent variable) and Teacher Performance (devendent variable). The data collection technique in this study is to use a questionnaire. The analysis technique in testing the hypothesis of this study is statistics using the SPSS (statistical for windows realease) program, from the results of the author's research based on the t test it is known that the t value is 7.963> t table 1.692 so that Ho is rejected and Ha is accepted which means the proposed hypo thesis is accepted. So it can be concluded that Work Conflict has a Significant Effect on Teacher Performance at Sinar Harapan Education Foundation. Beringin Regency. Deli Serdang. The percentage of the influence of Work Conflict on Teacher Performance with R2 is 65.8% and the remaining 34.2% is influenced by other variables outside this study, namely: incentives, motivation and abilities.